The Effectiveness of Betle Leaf (Piper betle L.) Extract as a Bio-pesticide for Controlled of Houseflies (Musca domestica L.) - Yushananta, Prayudhy; Ahyanti, Mei (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The housefly, Musca domestica L., spreads disease by contaminating food. However, chemical insecticides used to combat houseflies can pollute the environment and can harm non-target insects and humans; this demands safer alternatives and pest control options. AIM: This study aims to evaluate the effectiveness of Piper betle L. leaf extract as a bio-pesticide against houseflies. METHODS: This study using a factorial design with six variations in concentration (0%, 5%, 10%, 15%, 20%, and 25%), four variations in contact time (15, 30, 60, and 120 minutes), and 5-day-old M. domestica adults that were bred from residential areas. RESULTS: The results show that mortality was affected by concentration (p-value < 0.000), contact time (p-value < 0.000), and the interaction between concentration and contact time (p-value = 0.0007). Of the three, concentration had the greatest effect. CONCLUSION: As such, the use of Piper betle L. extract is a suitable, cheap, and environmentally safe method for controlling M. domestica.